Implementation of the Suzuki Method in the Cognitive Development of Classical Piano Students at Purwacaraka Music Studio in Surabaya - Alsadan Putra Sallawa (Universitas Negeri Surabaya, 2026)
This study aims to analyze the application and impact of the Suzuki method on children’s cognitive development in classical piano courses at Purwacaraka Music Studio in Surabaya, specifically at the Rungkut branch. This study employs a qualitative approach that emphasizes in-depth observation to understand a phenomenon, supplemented by observation, interviews, and documentation, focusing on the formal aspects of cognitive development and the learning materials used by children enrolled in classical piano courses. The five main aspects[i] applied in the Suzuki method for music education include teaching music reading, creating a pleasant practice environment for children, fostering the habit of listening to recordings, providing guidance through private lessons, and an educational system focused on talent development. These findings were obtained after the data were analyzed through data reduction, data presentation, and conclusion drawing. These findings were obtained after the data were analyzed through data reduction, data presentation, and conclusion drawing. To ensure the credibility of the research results, data validity was assessed using source and method triangulation. The application of the pedagogical system is influenced by several key factors, including student factors, musical instruments, playing techniques, and the concept of individuality derived from Dr. Pono Banoe’s “Music Class Method” theory. Cognitive development was examined based on Jean Piaget’s theory, covering conservation, decentring, classification, animism, series and transitivity, and reversibility. This study found that applying the Suzuki method enhances children’s cognitive development.